2020
DOI: 10.1021/acsomega.0c01151
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Geographical Location on the Metabolic Production of Giant Barrel Sponges (Xestospongia spp.) Revealed by Metabolomics Tools

Abstract: Despite their high therapeutic potential, only a limited number of approved drugs originate from marine natural products. A possible reason for this is their broad metabolic variability related to the environment, which can cause reproducibility issues. Consequently, a further understanding of environmental factors influencing the production of metabolites is required. Giant barrel sponges, Xestospongia spp., are a source of many new compounds and are found in a broad geographical range. In this study, the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…In relation to the use of MS and NMR spectra, in several studies of metabolomic applications on sponges and their associated microbes, the spectra data are then analyzed with the help of MS or NMR spectra databases available in the spectral data library using a SA. Currently, a SA analysis has been developed into a molecular networking analysis which is very helpful in analyzing chemical structures obtained through MS or NMR spectra data (Bayona et al, 2020;Kouchaksaraee et al, 2020;Olatunji et al, 2021;Storey et al, 2020).…”
Section: Objectives Of Metabolomics Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the use of MS and NMR spectra, in several studies of metabolomic applications on sponges and their associated microbes, the spectra data are then analyzed with the help of MS or NMR spectra databases available in the spectral data library using a SA. Currently, a SA analysis has been developed into a molecular networking analysis which is very helpful in analyzing chemical structures obtained through MS or NMR spectra data (Bayona et al, 2020;Kouchaksaraee et al, 2020;Olatunji et al, 2021;Storey et al, 2020).…”
Section: Objectives Of Metabolomics Researchmentioning
confidence: 99%
“…Almost all research on the application of metabolomics for quality control on sponges and their associated microbes is related to the environment in which they grow which later affects the chemical profile of both the MS and NMR spectra. This way, to conduct metabolomic research on the influence of the environment where sponges and their associated microbes grow, using the NMR or MS techniques combined with LC or GC, and PCA, PLS-DA, SA, and OPLS-DA, is recommended (Bojko et al, 2019;Bayona et al, 2018Bayona et al, , 2020Fiore et al, 2017;Mehbub et al, 2016;Reverter et al, 2018;Ternon et al, 2017Ternon et al, , 2016.…”
Section: Objectives Of Metabolomics Researchmentioning
confidence: 99%
“…Recent studies have applied non-targeted metabolomics to probe intraspecific, interspecific, and environmental variation of metabolite profiles in sponges. For example, the metabolomes of various species of Xestospongia were found to differ across four geographical locations and several metabolites were associated with specific environmental conditions [ 50 ]. In another study, seasonal changes as well as responses to increased water temperature were observed in the metabolomes of Haliclona fulva and H. mucosa [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the hunt for new bioactive compounds and natural products, metabolomics, especially liquid chromatography high-resolution mass spectrometry (LC-HRMS) based analysis, has gained interest owing to its capacity to analyze large numbers of metabolites simultaneously as well as its high sensitivity, reducing the amount of biological material necessary ( Paul et al, 2019 ). In sponge research metabolomics has been used to study differences in the metabolome depending on geographical location Bayona et al (2020) , between species Olsen et al (2016b) , Reverter et al (2018) or to investigate the chemical diversity of sponge extracts ( Cantrell et al, 2019 ; Mohanty et al, 2020 ). However, very few systematic investigations of method development for metabolomics of sponges have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, factors such as sampling, quenching the metabolism, storage conditions as well as sample extraction parameters have great effects on the final metabolome as well as data quality Engskog et al (2016) , Vuckovic (2018) , and have been investigated and reviewed for plasma, serum and urine Bi et al (2020) , González-Domínguez et al (2020) , Smith et al (2020) , mammalian cells Dettmer et al (2011) , Bi et al (2013) , Engskog et al (2015) , bacteria and microbes Mashego et al (2007) , Rabinowitz (2007) , Kapoore and Vaidyanathan (2018) , as well as for plants ( Kim and Verpoorte, 2010 ; Rodrigues et al, 2019 ; Salem et al, 2020 ). For the collection of sponges for metabolomics, no guidelines or practical consensus exist and the procedures for sampling varies, in some cases the sponges are frozen directly upon collection, in some cases the time between collection and freezing is not stated in the publications and in some cases the sponges are immediately stored in ethanol where after the ethanol is often discarded prior to extraction of the sponge ( Olsen et al, 2016b ; Einarsdottir et al, 2017 ; Bayona et al, 2018 ; Bayona et al, 2020 ; Reverter et al, 2018 ; Mohanty et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%